GROUNDWATER POTENTIAL OF THE ISLAND OF CRETE. PROBLEMS AND PERSPECTIVES. - Περλέρος B.; Παπαμαστοράκης Δ.; Κριτσωτάκης M.; Δρακοπούλου E.; Παναγόπουλος A. (Bulletin of the Geological Society of Greece, 2004)
This paper presents, reviews and evaluates the latest views and researches carried out on groundwater resources potential of the island of Crete. Data on the overall water budget of the island are provided, whilst information is also furnished on the actual water demands and the current percentage these are met. Comments and proposals are made towards further rational management of the documented rich groundwater potential of the island along with proposals on the utilization of the considerable surface runoff waters in the form of off-course basins and dams. The distinctiveness of the Water District of Crete, in comparison with the rest Districts of Greece, lays on the fact that it is the only one for which an Integrated Water Resources Management study exists that was compiled in the period 2000-2001. Elaboration of this study was assigned by the Regional Authority of Crete, Directorate for Planning and Development, Section of Water Resources Management, to the consorting consultancy firms of PAPAGRIGORIOU S., KAIMAKI S, PARLEROS V., PAPAGEORGIOU N, LAZARIDES and Ass., ATEM, with special scientific consultation from the firms ENVECO S.A. and WL/DELFT HYDRAULICS of Netherlands, on December 1999 following an international procurement.